The Effect of a Handball Warm-Up Program on Dynamic Balance among Elite Adolescent Handball Players - Abdolhamid Daneshjoo; Ali Hoseinpour; Hassan Sadeghi; Aref Kalantari; David George Behm (MDPI AG, 2022)
This study examined the effect of the handball warm-up program (HWP) on dynamic balance among elite adolescent handball players. In this case, 24 handball players were randomly assigned into experimental warm-up and control groups. The HWP was performed over 8 weeks (3 times per week). Dynamic balance before and after the intervention training programs were measured by the Biodex Balance System (BBS) and Y Balance test for the dominant (DL) and non-dominant legs (non-DL). After HWP training, BBS scores significantly improved in the overall (OSI) (30.4% and 31.1%), anterior-posterior (APSI) (44.6% and 35.2%), and medial-lateral stability indexes (MLSI) (38.8% and 43%) for both DL and non-DL. Post-training, the Y Balance test exhibited significant improvements in OSI (13.2% and 10.6%), anterior (17.2% and 12.6%), posteriolateral (12.8% and 11.3%), and posteriomedial stability indexes (9.2% and 7.9%) with DL and non-DL, respectively. In conclusion, dynamic balance improved overall after eight weeks of the HWP, with this improvement significantly greater with the trained versus the control group. Optimal balance during handball is an important factor to ensure coordinated and efficient movements and it is speculated that improved balance could positively impact injury prevention. Hence, the HWP program can be used as an alternative to a conventional warm-up program.